Cloud computing security threat with quantum key distribution defense model - Khalid, Roszelinda; Ahmad Zukarnain, Zuriati (Society of Digital Information and Wireless Communications (SDIWC), 2015)
Cloud computing offer the cost-effective and flexibility to the user. However, the security threat is a main concern for user to place their data in the cloud. Data that stored and shares through cloud have to be confidential and restricted. Information leakage, men in the middle attack are the two main issues that make information stored in the cloud insecure. Widely authentication method used is the classical approach like Public Key Infrastructure (PKI). This approach is workable in order to provide a secure environment within the cloud clients. The existing of Certificate Authority that act as controller they can verify the legal user. However, in certain circumstances, this approach cannot solve the issue such as stealing the identity. In this paper we are proposing a model that use quantum mechanical theory. This theory is supporting the no cloning theory. It used the power of light and a single photon to provide an authentication key. Throughout this paper, we also do a literature on various security threats, and authentication method in cloud. Then, we are introducing a quantum defense model as a solution of the listed threats. We proposed new cloud authentication architecture for cloud computing environment. A new cloud authentication environment that implements quantum mechanics is proven that can gain more trust with less time of computation in cloud communications.